Earth Systems and Environment - Earth Systems and Environment (Springer Nature, 2026)
Earth Systems & Environment (ESEV) publishes peer-reviewed original and review articles on the entire range of Earth systems and environment in order to further our understanding of the natural workings and various processes and interactions that govern the Earth systems in response to complex environmental problems caused by natural and human-induced forcings.
FI 1.36
Q1
Keywords: Earth; Space & Environmental Sciences; Environmental Geoscience; Geociencia; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Sistemas terrestres; Hidrosfera; Litosfera; Riesgos geoambientales